GAMBARAN TINGKAT KECEMASAN ANAK USIA PRASEKOLAH SAAT PEMASANGAN INFUS DI RUMAH SAKIT BAYUKARTA KARAWANG - Triana, Hani; Fauziah, Liliek; Horasniari Purba, Lemmy (Jurnal Sehat Masada, 2025)
Hospitalization in children is a process for some emergency reason or requires the child to stay in the hospital to undergo therapy and care until returning home. Children also have high anxiety when undergoing invasive procedures such as intravenous fluids or treatment carried out in the hospital with their reactions that tend to vary. Based on the researcher's experience, this also happened at Bayukarta Hospital, Karawang. This research method is a descriptive study using a cross-sectional approach. The population in this study were all preschool children who would undergo intravenous fluid (infusion) procedures with accidental sampling techniques, and data measuring instruments in the form of HARS questionnaires to measure the level of anxiety in children. The results of the study on 35 preschool children who underwent intravenous fluid (infusion) procedures at Bayukarta Hospital, Karawang showed that 2 children (5.7%) experienced severe anxiety while 33 children (94.3%) experienced panic. In conclusion, most preschool children who underwent intravenous fluid (infusion) procedures at Bayukarta Hospital experienced panic. Suggestions for Bayukarta Hospital Karawang can be used as input in creating strategies such as establishing relationships with therapeutic communication, conducting play therapy such as role-play, and involving people closest to reduce anxiety levels.